Simple synthesis of ZnSe nanoparticles by thermal treatment and their characterization - Salem, Aeshah Nizar; Saion, Elias; Al-Hada, Naif Mohammed; Mohamed Kamari, Halimah; Shaari, Abdul Halim; Radiman, Shahidan (Elsevier, 2017)
A simple thermal treatment was used to synthesize ZnSe nanoparticles at different calcination temperatures in a nitrogen flowing. The samples of ZnSe nanoparticles were prepared by reacting zinc nitrate (source of zinc) and selenium powder with Polyvinylpyrrolidone (capping agent). Analysis of their X-ray diffraction patterns suggested the formation of an amorphous phase of the unheated material before calcination, which then transformed into a cubic crystalline structure of ZnSe nanoparticles after calcination. The phase analyses using energy-dispersive X-ray spectroscopy and Fourier-transform infrared spectroscopy confirmed the presence of Zn and Se as the original compounds of prepared ZnSe nanoparticle samples. The average particle size of the samples increased from 7 ± 5 to 18 ± 3 nm as the calcination temperature was increased from 450 to 700 °C, which is also supported by the transmission electron microscopy results. Diffuse UV–visible reflectance spectra were used to determine the optical band gap through the Kubelka–Munk equation; the energy band gap was found to decrease from 4.24 to 3.95 eV with increasing calcination temperature.